A clinical study of neonatal outcome in pregnancy-induced hypertension - Lakshmikanth, J; C, Ashoka; S, Usha Rani (Indian Journal of Child Health, 2019)
Background: Pregnancy-induced hypertension (PIH) includes hypertensive disorders peculiar to pregnancy that have their onset during pregnancy and subsides completely following delivery. In India, perinatal mortality rate (PNMR) in PIH is high as the emphasis is still on maternal salvage, and there is lack of tertiary care centers dealing with premature and low-birth-weight infants. Objective: The objective of the study was to determine the extent of perinatal problems and to evaluate the prognostic significance of various factors associated with PIH on perinatal outcome and determine its effects. Materials and Methods: The study included 200 consecutive births which took place from March 2018 to February 2019 on mothers admitted with PIH in District Hospital, Tumkur, Karnataka. Results: The incidence of PIH was 8.6% in this study. The incidence of preterm was 31% which was high in eclampsia (63). PNMR in the study is 345/1000 which is higher than in general PNMR of the hospital. Conclusion: PIH is a multisystem disease and threat to the well-being of the mother and her unborn child. Characterization of the neonatal consequences of maternal hypertension is complicated by the administration of antihypertensive and anticonvulsant medications to the mother; thus, the fetal outcome might be influenced by both maternal disease and pharmacological intervention.